SDOCT Thickness Measurements of Various Retinal Layers in Patients with Autosomal Dominant Optic Atrophy due to OPA1 Mutations. (19th August 2013) - Schild, Andrea M.; Ristau, Tina; Fricke, Julia; Neugebauer, Antje; Kirchhof, Bernd; Sadda, Srinivas R.; Liakopoulos, Sandra
Abstract : Purpose . To specify thickness values of various retinal layers on macular spectral domain Optical Coherence Tomography (SDOCT) scans in patients with autosomal dominant optic atrophy (ADOA) compared to healthy controls. Methods . SDOCT volume scans of 7 patients with ADOA (OPA-1 mutation) and 14 healthy controls were quantitatively analyzed using manual grading software. Mean thickness values for the ETDRS grid subfields 5–8 were calculated for the spaces neurosensory retina, retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), a combined space of inner plexiform layer/outer plexiform layer/inner nuclear layer (IPL+INL+OPL), and a combined space of outer nuclear layer/photoreceptor layers (ONL+PL). Results . ADOA patients showed statistically significant lower retinal thickness values than controls (P < 0.01 ). RNFL (P < 0.001 ) and GCL thicknesses (P < 0.001 ) were significantly lower in ADOA patients. There was no difference in IPL+INL+OPL and in ONL+PL thickness. Conclusion . Manual subanalysis of macular SDOCT volume scans allowed detailed subanalysis of various retinal layers. Not only RNFL but also GCL thicknesses are reduced in the macular area of ADOA patients whereas subjacent layers are not involved. Together with clinical findings, macular SDOCT helps to identify patients with suspicion for hereditary optic neuropathy before genetic analysis confirms the diagnosis.